Operational Excellence within Sustainable Development Concept-Systematic Literature Review - Wojtkowiak, Daniel; Cyplik, Piotr (Sustainability, 2020)
The following paper was developed with a view to identifying the relationship between Sustainable Development and Operational Excellence concepts and to assess the state-of-the-art in Operational Excellence within Sustainable Development concept. Highly unstable business environments and opportunities occurring in the market require a specific approach and knowledge to achieve success. It is the authors’ view that improvements in the delivery of sustainable results through social, environmental, and economic responsibility is possible thanks to modern management concepts, strategies, and tools. These activities and approaches, when properly incorporated, significantly support the functioning of businesses in a responsible and profitable way. This paper outlines a systematic literature review of the subject described above. The literature review has been conducted with the use of two databases: Web of Science and Scopus. The results of the analysis show that there is a visible connection between Operational Excellence and Sustainable Development concepts. On the basis of the review, one can notice a strong relationship between Operational Excellence and management concepts, e.g., Lean Management. Nevertheless, the input of the selected articles based on abstract analysis compared to the whole compilation concerning Sustainable Development shows that there is a gap. The authors believe that this topic is interesting and worth further analysis.